Die problematiek rondom die lied van die NG Kerk: enkele bevindings vanut 'n sosiaal - wetenskapleke invalshoek (Acta Theologica)
This article investigates viewpoints regarding the hymn of the Dutch Reformed Church over the lase few decades by way of a document analysis of polemics from Die Kerkbode, the official publication of the DRC. Historically, there has always been conflict around the hymnic tradition of the Dutch Reformed Church, manifesting specifically as resistance against the official church-hymn. The longing for a simpler, experience-oriented hymn was stimulated especially by rhe influence of 19rhcentury Revival hymnody, a tendency still applying roday. An analysis of the polemics involved reveals that the duality within the hymnic practice of the DRC has co do particularly with two clashing types of devoutness within the church. Those opposing the official church-hymn are particularly burdened by the "unsingabilicy" of the melodies, as well as the fact char these hymns are foreign to the field of experience of the 20th-century person. The thesabilicy of an ecclesiastical identification with contemporary secular culture is however a complex question which also involves controversy regarding the retention of the true reformed nature of the church.